Impact of water management practices on productivity of soybean + maize intercropping system in Chambal command - Narolia, R.S.; Meena, Harphool; Singh, Pratap (Annals of Agricultural Research, 2016)
On-farm trials of soybean + maize intercropping system with improved water managementpractices were conducted during Kharif season from 2011 to 2014 at farmer's field of Left andRight main canal of Chambal command under Operational Research Programme (ORP) operatedby Agricultural Research Station, Kota. The main objective was to evaluate impact of Soybean +Maize intercropping system in the row ratio of 4:2 with improved water management practicesfor enhancing the productivity and economics of soybean crop. Two treatments were evaluated at12 locations and comprised of Improved water management practices i.e. two irrigations, first atfull branching and second at pod development stages by border strip (6 m x 50 m) method using80 per cent cut off ratio in soybean + maize intercropping system were compared with farmer'spractice i.e. flood irrigation method both in sole crop of soybean and maize at 12 locations. Resultsrevealed that soybean + maize intercropping system with improved water management practicesgave higher and sustainable soybean equivalent yield over the years compared to farmers practice.The mean soybean equivalent yield (1663 kgha-1) with 1.10 LER was 9.2 percent higher as comparedto farmers practice (1525 kgha-1). Pooled sustainability of soybean equivalent yield reflects thehigher sustainability yield index (0.808) and sustainability value index (0.802). Efficiency indicesfor water use, production efficiency and incremental benefit cost ratio were also found higher intest block over the control block.